Comparison of Prediction Models: Decision Tree, Random Forest, and Support Vector Regression - Putra, Kurnia Ramadhan (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
The Information Technology (IT) industry continues to grow rapidly, creating challenges in determining fair and competitive salaries for professionals. Accurate salary predictions are essential for companies to attract and retain talent while providing insights for individual career planning. This research aims to compare the performance of three machine learning models, such as Decision Tree Regression, Random Forest Regression, and Support Vector Regression in predicting IT sector salaries using demographic and professional data, including age, gender, education level, job position, and work experience. The study uses a dataset of 6,704 entries from Kaggle, with relationships between variables analyzed through statistical techniques such as Pearson Correlation and ANOVA. Model performance was evaluated using the R² Score, Root Mean Squared Error (RMSE), and Mean Absolute Error (MAE). Among the models, Random Forest Regression demonstrated the best performance, achieving the highest R² of 91.49% and an RMSE of 0.058, indicating high predictive accuracy with low error rates. Scatter plot visualizations confirm a strong correlation between actual and predicted salaries, supported by error analysis identifying minimal overestimation and underestimation cases. The research concludes that Random Forest Regression is the most effective model for IT salary predictions. These findings provide practical insights for organizations and individuals, highlighting the potential of data-driven approaches in salary determination. Future studies may focus on hyperparameter optimization and incorporating additional features to improve model performance and generalizability further improve model performance and generalizability.